Violence against women : an analysis of the epidemiology and patterns of injury in rape homicide in Cape Town and in rape in Johannesburg - Martin, Lorna Jean (Division of Forensic Medicine and Toxicology, 2019)
Violence against women is an important cause of morbidity and mortality in South Africa and indeed the of world. Women and men are equal and must have equal guarantees of economic, social, civil, political cultural rights. Women who are denied basic right security cannot participate equally in society. Violence denies this basic human right. This study is descriptive and a retrospective analysis of rape survivors in Johannesburg from 1992, a prospective analysis of homicide victims from Cape from mid-1996 to end 1998. The results have been analysed into demographic variables and compared to trends from the rest of the world. The epidemiology and pattern of injury violent crimes have specifically targeted. The main findings were: 1. incidence of rape in Johannesburg in 1992 was 165 per 100 000 women. 2. Rape in Johannesburg is seasonable and occur mainly in young African women, by strangers. 3. Approximately one third of survivors sustain non-genital as well as genital injury. 4. Most injuries can be classified as minor or moderate and comprise contusion, abrasions and lacerations. 5. The incidence of rape homicide in Town is 7.2 per 100 000 women, which represents a fatal sexual rate 1.23%. 6. The majority of rape homicide victims were coloured women in the group 26 to 45 years. 6. Of those murdered by people known to them, a current or ex-intimate partner murdered 18.6%. 7. 98.3% of rape victims had non-genital injury, and 55.9% had evidence of genital injury. 9. Most rape homicides have evidence of mechanical asphyxiation included in the mechanism of death. 10. The body areas most targeted by perpetrators in sexual assault are the head, neck and upper limbs. 11. The majority of the minor genital injuries comprise abrasions and lacerations to the posterior fourchette and introitus.